Safety and efficacy analysis of neoadjuvant radiotherapy combined with concurrent paclitaxel plus nedaplatin versus other platinum-based chemotherapy for thoracic segmental esophageal squamous cell carcinoma - Zhuang, Qingyang; Li, Hui; Tang, Lirui; Zheng, Hongying; Li, Jiancheng; Wu, Junxin; Li, Jinluan (Frontiers in Oncology, 2025)
BackgroundEsophageal cancer is among the leading causes of cancer-related mortality in males. This study aimed to evaluate the efficacy and safety of nedaplatin (NDP) in comparison to other platinum-based (OPB) agents combined with paclitaxel and concurrent neoadjuvant radiotherapy for locally advanced thoracic segmental esophageal squamous cell carcinoma (ESCC).MethodsThis single-center, retrospective cohort study was conducted in China. The primary endpoints of this study were safety and efficacy assessments. Unpaired t-tests, chi-squared tests, and Fisher’s exact tests were used to compare intergroup differences, as appropriate. Multivariate logistic regression models were used to explore the associations between postoperative outcomes and the two treatment groups. Kaplan–Meier survival curves and Cox proportional hazards regression models based on OS and PFS were used to compare the efficacy between the two groups.ResultsA total of 212 patients were enrolled in this retrospective cohort study, including 79 who received NDP and 133 who received OPB (82 were treated with cisplatin, 20 with carboplatin, 19 with lobaplatin, and 12 with oxaliplatin) agents. The incidences of grade 3–4 acute radiotherapy-associated esophagitis, pneumonitis, and leukemia were significantly lower in the NDP group than in the OPB group (p = 0.02, p < 0.001, and p = 0.002, respectively). All grades of acute gastrointestinal reactions, including nausea, vomiting, anorexia, and diarrhea, were significantly more frequent in the OPB group than in the NPD group (p < 0.001, p = 0.032, p < 0.001, and p = 0.002, respectively). The Kaplan–Meier curves for overall survival (OS) and progression-free survival (PFS) showed similar results for both groups.ConclusionsThe safety profile of nedaplatin may be superior to those of other platinum-based agents in terms of acute radiotherapy toxicity and postoperative side effects; however, there was no difference in the efficacy between the two groups regarding short-term prognostic tumor regression grades or long-term OS and PFS.